The biogeography of the mucosa-associated microbiome in health and disease - Sternes, Peter R.; Shah, Ayesha; Ayala Pintos, Camila; Fairlie, Thomas; Koloski, Natasha; Kang, Seungha; Tousignant, Kaylyn D.; McIlroy, Simon J.; Morrison, Mark; Tyson, Gene W.; Holtmann, Gerald J. (Frontiers in Microbiology, 2024)
ABSTRACT Little is known about the biogeography of the mucosa associated microbiome (MAM) in patients with inflammatory bowel disease (IBD) versus controls in different segments of the gastrointestinal tract, as well as the links between the MAM, gastrointestinal symptoms, and use of proton pump inhibitors (PPI). We recruited 59 controls (without structural abnormalities and gastrointestinal symptoms), 44 patients with ulcerative colitis (UC) and 31 with Crohn’s disease (CD). Biopsies from various segments of the upper and lower gastrointestinal tract were collected. Microbial composition was assessed via 16S rRNA gene amplicon analysis and the bacterial load of the mucosal biopsies were assessed via qPCR. The MAM was examined in the context of disease status, PPI usage, the severity of gastrointestinal symptoms, and the symptom response to a standardised nutrient challenge (SNC). Microbial communities of the MAM in the upper and lower gastrointestinal tract differed. IBD patients were characterised by relative and absolute depletion of numerous genera known to produce butyrate and/or propionate, with the largest differentiation being the depletion of Faecalibacterium in the lower gastrointestinal tract of CD patients. Additionally, PPI users exhibited an enrichment of Faecalibacteriumin the lower gastrointestinal tract. The severity of gastrointestinal symptoms, as well as the symptom response to the SNC, were significantly associated with MAM composition in the gastrointestinal tract. Quantitative changes of bacterial taxa along the gastrointestinal tract indicates that MAM can be targeted in specific segments of the GI tract to improve patient outcomes.